2021
DOI: 10.1161/strokeaha.120.031514
|View full text |Cite
|
Sign up to set email alerts
|

European Multicenter Study of ET-COVID-19

Abstract: Background and Purpose: Acute ischemic stroke and large vessel occlusion can be concurrent with the coronavirus disease 2019 (COVID-19) infection. Outcomes after mechanical thrombectomy (MT) for large vessel occlusion in patients with COVID-19 are substantially unknown. Our aim was to study early outcomes after MT in patients with COVID-19. Methods: Multicenter, European, cohort study involving 34 stroke centers in France, Italy, Spain, and Belgium. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 29 publications
4
43
1
2
Order By: Relevance
“…53 European Multicenter Study of ET-COVID-19 also pointed out a higher rate of 30-day mortality (29%) after MT among patients with AIS with COVID-19. 54 We need immediate consideration of a new streamline of MT for AIS-LVO with COVID-19 in the contexts of the pandemic evolution. 52 56 SKIP used lower dose of tPA (0.6 mg/kg).…”
Section: Expected Completion Datementioning
confidence: 99%
“…53 European Multicenter Study of ET-COVID-19 also pointed out a higher rate of 30-day mortality (29%) after MT among patients with AIS with COVID-19. 54 We need immediate consideration of a new streamline of MT for AIS-LVO with COVID-19 in the contexts of the pandemic evolution. 52 56 SKIP used lower dose of tPA (0.6 mg/kg).…”
Section: Expected Completion Datementioning
confidence: 99%
“…During 2020, a new risk factor for stroke occurrence has emerged related to COVID-19. Some reports indicated that COVID-19-related strokes are more severe and occur in younger patients than usual strokes, probably owing to coagulation abnormalities induced by SARS-CoV-2 infection [ 5 , 6 ]. The incidence of stroke in COVID-19 patients ranges from 1% to 6% [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…While some studies reported on young patients in their thirties with an obvious male predominance, 5 , 10 other studies reported a high frequency of MT in older male COVID-19 patients with a median age of more than 70 years. 13 15 Overall, according to a meta-analysis of 50 studies, COVID-19 patients with acute cerebrovascular disease were found to be younger than stroke patients with no SARS-CoV-2 infection (pooled median difference=6.0 y). 16 In a parallel manner, COVID-19 patients who underwent mechanical thrombectomy were younger than uninfected patients who underwent MT during both the pandemic 6 and before the pandemic (Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“… 17 Interestingly, in addition to being younger, some studies on MT reported many COVID-19 patients with AIS lacking traditional vascular risk factors, 5 , 10 although many other studies described the presence of these risk factors (eg, hypertension, diabetes and cardiovascular disease) in COVID-19 patients treated with MT. 6 , 13 15 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation